Development of Coastal Protection Scheine Database for Peninsular Malaysia - Muhammad Aminuddin Zulkefli, Muhammad Aminuddin (Universiti Teknologi Petronas, 2010)
To improve the systems, the author is taking initiative to create a database scheme of coastal protection along the Peninsular Malaysia coastline. The gathering of this database is hoped to develop better understanding on design criteria about coastal protection scheme along Peninsular Malaysia coastlines performances and failure mode of structure. In presenting the database of coastal protection scheme along Peninsular Malaysia's shoreline, software called GIS (MapInfo Professional 7.0®) is used.